2019
DOI: 10.3847/1538-4357/ab3804
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Inside-out Galaxy Growth and Quenching of a z ∼ 2 Compact Galaxy From High-resolution Molecular Gas Imaging

Abstract: We present high spatial resolution imaging of the CO(1-0) line from the Karl G. Jansky Very Large Array (VLA) of COSMOS 27289, a massive, compact star forming galaxy at z = 2.234. This galaxy was selected to be structurally similar to z ∼ 2 passive galaxies. Our previous observations showed that it is very gas-poor with respect to typical star-forming galaxies at these redshifts, consistent with a rapid transition to quiescence as the molecular gas is depleted. The new data show that both the molecular gas fra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 95 publications
7
17
2
Order By: Relevance
“…For example, Morselli et al (2019) found that star formation is centrally enhanced in galaxies near the star-forming sequence and centrally suppressed below it. In agreement with this work, several authors have found that galaxies not only form inside-out but also quench from the inside-out (Ellison et al 2018;Nelson et al 2016;Li et al 2015;Rowlands et al 2018;Spilker et al 2019). Using the MaNGA survey (Bundy et al 2015;Yan et al 2016), Lin et al (2019) find that the fraction of galaxies quenching inside-out grows with mass (see also Belfiore et al 2018).…”
supporting
confidence: 66%
“…For example, Morselli et al (2019) found that star formation is centrally enhanced in galaxies near the star-forming sequence and centrally suppressed below it. In agreement with this work, several authors have found that galaxies not only form inside-out but also quench from the inside-out (Ellison et al 2018;Nelson et al 2016;Li et al 2015;Rowlands et al 2018;Spilker et al 2019). Using the MaNGA survey (Bundy et al 2015;Yan et al 2016), Lin et al (2019) find that the fraction of galaxies quenching inside-out grows with mass (see also Belfiore et al 2018).…”
supporting
confidence: 66%
“…Spatially resolved studies have suggested that the massive star-forming galaxies at z ; 1−2 exhibit a rising specific star formation rate (sSFR; SFR per unit stellar mass) profile from their center to the outskirts, indicating that the fade out of star formation commences from the galactic center (e.g., Tacchella et al 2015Tacchella et al , 2018Nelson et al 2016;Spilker et al 2019). Such an "inside-out" process of quenching can also be reproduced within the context of cosmological simulation (Tacchella et al 2016).…”
Section: Introductionmentioning
confidence: 92%
“…The cool gas taking part in these outflows is the raw material from which stars are formed, so its fate may affect the evolution of the host galaxies. Fast outflows are among the leading internal negative-feedback processes to explain the rapid ( 10 9 years) inside-out cessation ("quenching") of star formation in massive galaxies (Schawinski et al 2014;Onodera et al 2015;Tacchella et al 2015Tacchella et al , 2016Spilker et al 2019). However, simply carrying the cool gas out of the galaxy and depositing it into the circumgalactic medium (CGM; Tumlinson et al 2017) may not be sufficient to quench these galaxies since the cool material, if left alone, will eventually fall back onto the galaxy and form new stars.…”
Section: Setting the Scenementioning
confidence: 99%